Infratentorial Relapsing Neuroglial Tumors in Adults: Management and Unsolved Issues—A Systematic Review - Lara Brunasso; Chiara Avallone; Ada Maria Florena; Giovanni Grasso (Brain Sciences, 2024)
(1) Background: Gangliogliomas are rare tumors accounting for about 0.4% of all central nervous system tumors. They are usually located in the temporal lobes of children and young adults, though such tumors in the infratentorial region and adult-age patients rarely reported. (2) Methods: A systematic review on ganglioglioma with infratentorial location in the adult population was conducted in accordance with the PRISMA guidelines. A total of 275 articles were found, and 23 were included. Demographic data, the location and histology of the lesion, pre-operative neurological status, the type of surgery, recurrence, radiotherapy/chemotherapy adjuvant treatments, neurological outcomes and follow-up information were collected. We also presented an illustrative case. (3) Results: A total of 27 patients were included. In 51%, the location was the cerebellum; in 40%, it was the fourth ventricle; in 11%, it was brainstem; and in 4%, it was the cerebellopontine angle. STR was performed in 44%, GTR in 26% and biopsy in 15% of the cases. Adjuvant radiotherapy was found in 22% of cases. Disease recurrence occurred in 15% of patients between 1 and 12 months after surgery with a diagnosis of high-grade ganglioglioma, while in six cases, no disease recurrence was documented. (4) Conclusions: Infratentorial glioneuronal tumors are rare findings in the adult population. Histopathological characterization does not seem to fully reflect their true behavior. Future studies are warranted for better characterizing histopathological findings and treatment.